Spatial and temporal variations of summer hot days and heat waves and their relationships with large‐scale atmospheric circulations across Northeast China - Lei Wang; Wen J. Wang; Zhengfang Wu; Haibo Du; Xiangjin Shen; Shuang Ma (International Journal of Climatology, 2018)
This study investigated the recent and future spatiotemporal changes in summer hot days (HDs) and heat waves (HWs) and their relationships with large‐scale atmospheric circulations over Northeast China (NEC). We used daily maximum temperature data from 109 meteorological stations for the period 1961–2013 across NEC and the output of 11 general circulation models from Coupled Model Intercomparison Project Phase 5 under RCP4.5 and RCP8.5 emission scenarios. We found that the frequencies and intensities of summer HDs and HWs overall increased in the last 53 years. The increases mainly occurred in the northeastern Inner Mongolia, the north part of the Heilongjiang Province, and southern Changbai Mountains. The during time periods between the start and end dates of HDs were lengthened from 1961 to 2013 in the eastern Inner Mongolia, the northeastern Heilongjiang Province, and the southern Liaoning Province. Our results showed that HDs and HWs exhibited significant increasing trends from 2006 to 2100 under RCP4.5 and RCP8.5 emission scenarios. Generally, more frequent and intense summer HDs and HWs would happen in NEC over the 21st century. Especially, the northwest of NEC and the south and middle of Da Hinggan Mountains would experience the most frequent and intense HDs and HWs. The variations in atmospheric circulation in summers with abnormal frequency of HDs and HWs were driven by Asian Zonal Circulation and Western Pacific Subtropical High simultaneously. An anticyclonic circulation anomaly prevailing over the west of NEC and the higher summer surface sea temperature in Japan Sea resulted in more frequent HDs and HWs across NEC. This study may help to understand future changes in HDs and HWs and provide references for water resources management and policy‐making in agriculture and forestry.